Assessment of subclinical atherosclerosis in psoriatic arthritis patients without clinically overt cardiovascular disease or traditional atherosclerosis risk factor - Şule Apraş Bilgen; Umut Kalyoncu; Abdülsamed Erden; Uğur Canpolat; Levent Kılıç; Ömer Karadağ; Kudret Aytemir; Sedat Kiraz; Ali Akdoğan; İhsan Ertenli (KARE Publishing, 2018)
Objective: Cardiovascular disease (CVD) is more prevalent in almost all patients with chronic inflammatory musculoskeletal diseases than in their healthy counterparts. The aim of this study was to assess the presence of subclinical atherosclerosis in patients with psoriatic arthritis (PsA) in comparison with patients with rheumatoid arthritis (RA) and healthy controls. Methods: A total of 30 patients with PsA, 30 patients with RA, and 30 healthy controls were enrolled in this parallel group study. Demographic, clinical, and laboratory data of the groups were recorded. The Disease Activity Score-28 tool was used for joint assessment. The erythrocyte sedimentation rate and C-reactive protein level were measured as acute phase reactants. Flow-mediated dilatation (FMD) and carotid intima media thickness (CIMT) were also measured in all participants. Results: The median duration of disease in patients with PsA was 60 months (range: 8-216 months). A total of 22 of 30 (73.3%) PsA patients had a diagnosis of psoriasis and 13 (48.1%) had active disease. The study groups were similar with regard to age, gender, and body mass index data. In all, 23 (76.7%) of the PsA patients and 5 (16.7%) of the RA patients were using an anti-tumor necrosis factor alpha therapy (p<0.001). The FMD percentage was significantly smaller in both the PsA and the RA patients than in the healthy controls (p<0.001). The median CIMT was greater in the RA patients compared with the PsA patients and the healthy controls (p=0.008). There was no significant difference in FMD or CIMT between patients with and without an active joint lesion. Conclusion: Endothelial functions were impaired in PsA, as in RA, in the absence of conventional risk factors or overt CVD. This finding may show a potential association between PsA, atherosclerosis, and CVD.